2018
DOI: 10.1088/1361-648x/aaa5ea
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of Co4Sb12with Bi2Te3nanoinclusions

Abstract: The figure of merit (zT) of a thermoelectric material can be enhanced by incorporation of nanoinclusions into bulk material. The presence of bismuth telluride (Bi2Te3) nanoinclusions in Co4Sb12 leads to lower phonon thermal conductivity by introducing interfaces and defects; it enhances the average zT between 300-700 K. In the current study, Bi2Te3 nanoparticles were dispersed into bulk Co4Sb12 by ball-milling. The bulk was fabricated by spark plasma sintering (SPS). The presence of Bi2Te3 dispersion in Co4Sb1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…The electron is not easy to be scattered because of the size of the nanoscale second-phase is much larger than the mean free path of the electron, which has little effect on the electrical properties. The preparation of CoSb 3 -based nanocomposites by in-situ generation [78,[167][168][169][170][171][172][173][174][175][176][177] or mechanical addition of nanoinclusions [178][179][180][181][182][183][184][185][186][187][188][189][190][191][192][193] is a common method to introduce the second phase. In x Ce y Co 4 Sb 12 nanocomposites containing in-situ formed InSb nanophases (10-80 nm) were prepared by melt quenching, annealing, and spark plasma sintering [78], as shown in Figs.…”
Section: Low Dimensionalmentioning
confidence: 99%
See 1 more Smart Citation
“…The electron is not easy to be scattered because of the size of the nanoscale second-phase is much larger than the mean free path of the electron, which has little effect on the electrical properties. The preparation of CoSb 3 -based nanocomposites by in-situ generation [78,[167][168][169][170][171][172][173][174][175][176][177] or mechanical addition of nanoinclusions [178][179][180][181][182][183][184][185][186][187][188][189][190][191][192][193] is a common method to introduce the second phase. In x Ce y Co 4 Sb 12 nanocomposites containing in-situ formed InSb nanophases (10-80 nm) were prepared by melt quenching, annealing, and spark plasma sintering [78], as shown in Figs.…”
Section: Low Dimensionalmentioning
confidence: 99%
“…In x Ce y Co 4 Sb 12 nanocomposites containing in-situ formed InSb nanophases (10-80 nm) were prepared by melt quenching, annealing, and spark plasma sintering [78], as shown in Figs. 10(a [189], MoS 2 [190], etc.) in the CoSb 3 -based material, as shown in Figs.…”
Section: Low Dimensionalmentioning
confidence: 99%
“…This is not the case if the quadratic term in α is considered. If this point and the contribution of the chemical potentials are considered in J Q,i (formula (16) in [3]), then in the EMT formula only κ e,i and α i occur. Starting with J i and J Q,i and correcting these inaccuracies contained in Equation (A2), then it follows for the EMT formula…”
Section: Institutional Review Board Statement: Not Applicablementioning
confidence: 99%
“…As a theoretical support, the EMT formalism, which has been widely used to explain the transport properties of composites, including ceramics [13][14][15] and thermoelectrics [16][17][18], will be implemented.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have been focusing on the impacts of Bi 2 Te 3 -based alloy nanoparticles in improving the properties of TE materials. Jabar et al reported that introducing the isostructural Bi 2 Te 3 nanoparticles in the Bi 2 Te 2.7 Se 0.3 matrix was a good approach to optimize the TE transport parameters of the matrix through the construction of the coherent interfaces and the establishment of the interface potential barriers. Ghosh et al reported that the carrier concentration was increased because the Bi 2 Te 3 nanoparticles contributed electrons to the Co 4 Sb 12 matrix, and the power factor was improved. In addition, solid solutions of Bi 2 Te 3 and Sb 2 Te 3 are usually used to obtain p-type Bi 2 Te 3 -based materials (Bi x Sb 2– x Te 3 ).…”
Section: Introductionmentioning
confidence: 99%